Active control of a non-linear landing gear system having oleo pneumatic shock absorber using robust linear quadratic regulator approach - Yazici, Hakan; Sever, Mert (SAGE PUBLICATIONS LTD, 2018)
This paper deals with the active control of a non-linear active landing gear system equipped with oleo pneumatic shock absorber. Runway induced vibration can cause reduction of pilot's capability of control the aircraft and results the safety problem before take-off and after landing. Moreover, passenger-crew comfort is adversely affected by vertical vibrations of the fuselage. The active landing gears equipped with oleo pneumatic shock absorber are highly non-linear systems. In this study, uncertain polytopic state space representation is developed by modelling the pneumatic shock absorber dynamics as a mechanical system with non-linear stiffness and damping properties. Then, linear matrix inequalities-based robust linear quadratic regulator controller having pole location constraints is designed, since the classical linear quadratic regulator control design is dealing with linearized state space models without considering the non-linearities and uncertainties. Thereafter, numerical simulation studies are carried out to analyse aircraft response during taxiing. Bump-and random-type runway irregularities are used with various runway class and wide range of longitudinal speed. Simulation results revealed that neglecting the non-linear dynamics associated with oleo pneumatic shock absorber results significant performance degradation. Consequently, it is demonstrated that proposed robust linear quadratic regulator controller has a superior performance in terms of passenger-crew comfort and operational safety when compared to classical linear quadratic regulator.
Keywords: Active landing gear; oleo pneumatic shock absorber; taxiing performance; robust control; linear quadratic regulator; linear matrix inequalities; VIBRATION ANALYSIS; AIRCRAFT; DESIGN; MODEL; Engineering